Cues to Action to Utilization of Cervical Cancer Screening Services among Women of Reproductive age in Kediri, East Java, Indonesia (Indian Journal of Public Health Research & Development, 2020)
Cervical cancer is currently ranked among the top among the various types of cancer that causes deathin women in the world. The majority of women diagnosed with cervical cancer do not perform screeningtests or do not follow up after being found abnormal results. The purpose of this study was to determinethe correlation between cues to action or trigger and the implementation of early detection of cervicalcancer using Visual Inspection with Acetic Acid (VIA) method in Kediri, Indonesia. This study used a casecontroldesign. The sampling technique was a multi-stage random sampling method. The sample was 410respondents. The data were analyzed using logistic regression. The results showed that the trigger affectsthe implementation of early detection of cervical cancer using the VIA method. Based on the results, theOdds Ratio (OR) cues to action or trigger values were: 1) Information from high television was obtainedOR value: 2.7; 2) Recommendation from high physician was obtained OR: 2,3; 3) Recommendation frommidwife was obtained OR: 2.6; 4) The recommendation from a friend was obtained OR: 2.5; 5) Having everseen high cervical cancer patients was obtained OR: 1.6; 6) Having ever read a book or a high leaflet wasobtained OR: 1.8. It showed that the higher cues to action or trigger were given to the women, the higherthe probability of women to perform the early detection of cervical cancer using the VIA method. Basedon the results, the appropriate cues to action or trigger need to be selected to improve the behavior of earlydetection of cervical cancer VIA method in women.
Keywords: Cervical Cancer, Early Detection, Cues to Action.